Palliative and End-of-Life Care for Medical Residents (Out of Print) - Douglas Ross; Susan Wolfsthal (Association of American Medical Colleges, 2007)
Abstract Introduction Good care of patients at end-of-life can result in a meaningful period of personal growth for the patient and family, and a rewarding experience for the physician. While palliative care education in medical schools has improved over the past two decades, many internal medicine residents may not have encountered such content in medical school, this training program provides medical residents with a set of skills required for basic competency in palliative and end-of-life care. This foundational information can then be used in a variety of clinical settings either as part of skill building exercises or as a clinical resource. Since the course is web-based it can be accessed by participants at any time from any computer with internet access and they can complete the course at their own pace. Methods This course contains six units, on the topics of pain management; management of non-pain symptoms; communication; psychosocial, cultural, and spiritual issues; legal and ethical issues, and hospice care. Each unit is subdivided into modules and includes a pre- and posttest based on unit content. Each module includes an overview of the content, learning objectives to be achieved, links to relevant information, and readings and resources to augment module content. Upon successful completion of the course, participants can print a certificate of completion. Results Overall, the course was received favorably, with > 70% of all participants agreeing or strongly agreeing that the information was applicable to their clinical practice, and valuable to their education/training as a physician. Residents who were graduates of the authors' medical school (N = 45) and participated in our medical school's mandatory palliative care training program performed numerically better on the pretests for units I, II, and IV. Discussion This portable, web-based training targeted to the internal medicine resident as learner could easily be adapted for use by other residency programs worldwide.